Metabolomic Profiles and Heart Failure Risk in Black Adults: Insights From the Jackson Heart Study. (20th January 2021) - Tahir, Usman A.; Katz, Daniel H.; Zhao, Tianyi; Ngo, Debby; Cruz, Daniel E.; Robbins, Jeremy M.; Chen, Zsu-Zsu; Peterson, Bennet; Benson, Mark D.; Shi, Xu; Dailey, Lucas; Andersson, Charlotte; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Heart failure (HF) is a heterogeneous disease characterized by significant metabolic disturbances; however, the breadth of metabolic dysfunction before the onset of overt disease is not well understood. The purpose of this study was to determine the association of circulating metabolites with incident HF to uncover novel metabolic pathways to disease. Methods: We performed targeted plasma metabolomic profiling in a deeply phenotyped group of Black adults from the JHS (Jackson Heart Study; n=2199). We related metabolites associated with incident HF to established etiological mechanisms, including increased left ventricular mass index and incident coronary heart disease. Furthermore, we evaluated differential associations of metabolites with HF with preserved ejection fraction versus HF with reduced ejection fraction. Results: Metabolites associated with incident HF included products of posttranscriptional modifications of RNA, as well as polyamine and nitric oxide metabolism. A subset of metabolite-HF associations was independent of well-established HF pathways such as increased left ventricular mass index and incident coronary heart disease and included homoarginine (per 1 SD increase in metabolite level, hazard ratio, 0.77; P =1.2×10 −3 ), diacetylspermine (hazard ratio, 1.34; P =3.4×10 −3 ), and uridine (hazard ratio, 0.79; P, 3×10 −4 ). Furthermore, metabolites involved in pyrimidine metabolism (orotic acid) and collagen turnover ( N -methylproline) among others were part of a distinct metabolic signature that differentiated individuals with HF with preserved ejection fraction versus HF with reduced ejection fraction. Conclusions: The integration of clinical phenotyping with plasma metabolomic profiling uncovered novel metabolic processes in nontraditional disease pathways underlying the heterogeneity of HF development in Black adults.